Natural History of Nonoperatively Treated Osteochondral Lesions of the Talus. (January 2015) - Klammer, Georg; Maquieira, Gerardo J.; Spahn, Silke; Vigfusson, Vanessa; Zanetti, Marco; Espinosa, Norman
Background: We hypothesized that patients undergoing nonoperative treatment for asymptomatic or minimally symptomatic osteochondral lesions of the talus (OLTs) would not deteriorate clinically or radiologically over time. Methods: Forty-eight patients (mean age = 48 years; range, 13-78 years) with an OLT confirmed by magnetic resonance imaging (MRI) who had not undergone ankle joint surgery were retrospectively reviewed. All patients were evaluated after a minimum follow-up of 2 years (mean = 52 months; range, 27-124 months). All patients filled out an individual questionnaire and underwent a physical and radiographic assessment (radiograph and hindfoot MRI). Results: At final follow-up, 43 ankles (86%) in 41 patients were pain-free (visual analogue scale [VAS] 0, n = 12) or less painful (VAS 1-3, n = 31). Radiographically, osteoarthritis was absent in 47%, and grade 1 and 2 osteoarthritis each were found in 27% (van Dijk classification). Magnetic resonance imaging revealed no substantial progression in staging or lesion size. Pain at time of follow-up correlated with the depth of the lesion at initial MRI ( P < .05) and with subchondral cyst formation and presence or change of bone marrow edema at follow-up MRI ( P < .05). Conclusion: Minimally symptomatic OLTs did not appear to progress or worsen over time when treated nonoperatively. Level of Evidence: Level IV, case series.